(3OhQ GdeOjQ aj OYe GdeYde GdeHJOiA ZjQ GdeYO JQHhjGs - (3QVhGf, QaGg QeRjs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2014)
(3JfGhdJ GdOQGSI hGbY GdeYdejf GdeHJOFjf aj EMOi GdeOGQS GdNGUI aj efWbI LHd dHfGf hGdJYQa Ydi GdeTcdGJ GdJj JhGLg GdeYdejf GdeHJOFjf aj GdSfI GdChdi ef JYjjfge, HGdEVGaI Edi OQGSI OhQ GdeOjQ aj OYe GdeYde GdeHJOF hCKQ JfajP (B"(3HQfGeL EYOGO hJgjFI hOYe GdeYde GdeHJOF(B" (3Ydi JMSjf COGA GdeYdejf GdeHJOFjf hQaY GdeSJhi GdJMUjdj ddJdGejP(B. (3gPg GdOQGSI gj ef GdfhY GdELQGFj, MjK JeJ aj GdeQMdI GdChdi OQGSI eTcdGJ GdeYdejf GdeHJOFjf YHQ GdedGMXI dCOGFge aj GdUaha, OaGJQ JMVjQ GdOQhS hfJGFL JdGejPge, cPdc edGMXI GdeOjQ NdGd bjGeg HGdegGe GdEOGQjI, ceG Je GdJYeb HGdeTcdI ef NdGd ELQGA ebGHdGJ eY GdeOjQ hGdeYdejf GdNHQGA(B. (3haj GdeQMdI GdKGfjI Je GdJNWjW dHQfGeL EYOGO hJgjFI hOYe GdeYde GdeHJOF ef Ke JfajPg aj TgQ BPGQ HeTGQcI aQjb GdYed GdPj JeKd HGdeOjQ, GdeYdejf GdNHQGA, hGdeYdejf GdeHJOFjf, hHYO EJeGe JfajP GdHQfGeL, Je JMdjd GdfJGFL hCYjO ELQGA GdebGHdGJ eY GdeYdejf(B. (3EJVM aj GdeQMdI GdChdi YOe aYGdjI GdOhQ GdETQGaj GdPj jbhe Hg GdeOjQ aj GdeOQSI, hZjGH GdJOQjH Gdegfj bHd HOA GdeYdejf GdeHJOFjf HeeGQSI egGege hCKfGA GdNOeI CjVG, hYOe Jecf GdefSbjf ef eeGQSI OhQge GdETQGaj GdaqYGd(B. (3haj GdeQMdI GdKGfjI JHjf Cf GdHQfGeL SGge LRFjG aj JMSjf COGA GdeYdejf GdeHJOFjf, ceG SGge OYe GdeYdejf GdeHJOFjf CKfGA GdNOeI aj QaY GdeSJhi GdJMUjdj dJdGejPge HTcd LRFj NdGd GdaUd GdCNjQ ef GdYGe GdOQGSj(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Formation continue des enseignants; Gestion scolaire; Teachers in-service training School management; (3JOQjH GdeYdejf GdGOGQI GdeOQSjIs